Development of a Theoretical Model of Readiness for Independent Aging Based on Nutrition, Physical Activity, and Social Support among Pre-Elderly Adults: Pengembangan Model Teoretis Kesiapan Menua secara Mandiri Berdasarkan Gizi, Aktivitas Fisik, dan Dukungan Sosial pada Orang Dewasa Pra-Lansia - Istiqomah Dwi Andari; Riska Arsita Harnawati; Adevia Maulidya Chikmah (Journal of Health Sciences and Public Health, 2026)
The increasing proportion of the aging population has become a major public health challenge due to the growing prevalence of degenerative diseases and the decline in functional independence among older adults. Preparing individuals during the pre-elderly period is considered a strategic approach to promote healthy aging and prevent functional decline in later life. This study aimed to develop a theoretical model of readiness for independent aging based on the interaction of nutritional factors, physical activity, and social support among pre-elderly adults. A quantitative explanatory study with a cross-sectional design was conducted involving 50 pre-elderly respondents in Pagongan Village, Tegal Regency. Data were collected using standardized questionnaires and anthropometric measurements, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The simulation results demonstrated that all constructs met the requirements of validity and reliability, with Average Variance Extracted (AVE) values above 0.50 and Composite Reliability values above 0.70. The structural model showed good predictive ability (R² = 0.684; SRMR = 0.064), indicating that nutritional factors, physical activity, and social support explained 68.4% of the variance in readiness for independent aging. Physical activity was identified as the strongest determinant (β = 0.447; p < 0.001), followed by nutritional factors (β = 0.321; p = 0.001) and social support (β = 0.289; p = 0.003). The proposed theoretical model highlights that readiness for independent aging is a multidimensional construct influenced by biological, behavioral, and psychosocial determinants. This model provides a conceptual foundation for developing preventive strategies, health promotion programs, and future intervention studies aimed at supporting healthy aging and reducing the risk of degenerative diseases among pre-elderly populations.